PENGARUH WHISTLEBLOWING SYSTEM, SIKAP, DAN BUDAYA ORGANISASI TERHADAP PENCEGAHAN FRAUD DI BIDANG PERPAJAKAN - Alfiyyah Aini Khisma Authar, Aini (2021)
This study aims to examine the effect of the whistleblowing system, attitudes, and organizational culture on the prevention of fraud in the taxation sector. The dependent variable in this study is fraud prevention and the independent variables in this study are the whistleblowing system, attitudes, and organizational culture. This study uses primary data by distributing questionnaires. The sample used in this study were employees who worked at KPP Pratama Jakarta Cakung and involved 66 respondents with sample selection based on the Convenience Sampling technique. Hypothesis testing in this study was carried out through multiple linear regression analysis using SPSS 26 software. The results of this study indicate that the whistleblowing system has a positive effect on the prevention of fraud in the taxation sector, attitudes have a positive effect on the prevention of fraud in the taxation sector, and organizational culture has a positive effect on the prevention of fraud in the taxation sector. Keywords: whistleblowing system, attitude, organizational culture, fraud